Tackling food waste in the tourism sector: towards a responsible consumption trend - Delgado, Amélia (2023)
One of the significant problems of planet Earth is related to food production and consumption. This paper evaluates the role of the tourism sector in generating food waste as well as its potential to drive sustainability. Tackling food loss and waste is acknowledged as urgent, both for the people and the planet. Food waste is particularly problematic in industrialised regions, impeding the fulfilment of the Sustainable Development Goals. Although most of the wasted food originates in households, the contribution of the tourism sector is still relevant. A multidisciplinary reflection is thus carried out to assess the impacts of tourism on food production and consumption, linking them with cultural landscapes. By taking the UK as a case study, common problems of the sector are exposed, including dealing with food that remains uneaten, and the need to accurately assess food waste. Data gaps and guidance in measuring food waste are discussed, and suggestions for mitigating this issue include increasing food literacy, reducing food demand, and implementing sustainability business awards. Initiatives such as zero-waste restaurants are paving the way for mainstream changes in reducing food waste, thereby addressing climate change, increasing food availability and helping to alleviate hunger and malnutrition worldwide.